Pengaruh Pendekatan Somatis, Audiotori, Visual Intelektual (Savi) Berbasis Brain Gym Terhadap Hasil Belajar Kognitif Peserta Didik pada Materi Pencemaran Lingkungan - El Fiah, Rifda; Rinaldy, Rendy (Universitas Islam Negeri Raden Intan Lampung, 2015)
The author uses experimental research methods because the author will look for the effect of treatment (treatment) particular. The type of experiment used is Quasy Experimental Design, which has a control group but is not fully functional to control the outside variables that affect the implementation of the experiment. This research was conducted in class VII of SMP Negeri 13 Bandar Lampung consisting of 2 classes namely experimental class (VII E) applied Somatis Approach, Auditory, Visual, Intellectual (SAVI) based on brain gym to cognitive learning result and control class (VII A) Using learning methods of lectures and frequently asked questions. Data collection techniques are test (pretest and posttest), and documentation. There is a significant influence of Somatic, Auditory, Visual, Intellectual (SAVI) -based Brain Gym approach to cognitive learning outcomes in science learning especially in students of SMPN 13 Bandar Lampung. The achievement of improved cognitive learning outcomes can be seen from the pretest and posttest values, in the pretest grade control classes 63.75 and posttest 70.63 and the pretest average pretest grade of 69.06 and the posttest 77.03.